The Effect of Leadership Style and Human Resources Development on Employee Performance with Job Satisfaction as Intervening Variable - Muhammad Ridwan; Ramdani Bayu Putra; Joko Purwanto; Hasmaynelis Fitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to determine how much influence leadership style, human resource development has on employee performance at the Mukomuko district social service with job satisfaction as an intervening variable. Methods of collecting data through surveys and questionnaires. The analytical method used is validity and reliability test, multiple linear analysis, hypothesis testing using F test and t test. The total respondents in this study amounted to 55 respondents. Based on the research obtained based on the partial test (t test) obtained: (a) Leadership style has a positive and significant effect on job satisfaction. (b) human resource development has a positive and significant effect on job satisfaction. (c) Leadership style has a positive and significant effect on employee performance. (d) human resource development has a positive and significant effect on employee performance. (e) job satisfaction has a positive and significant effect on employee performance. Then the results of the coefficient of determination 0.592 or 59.2% this shows that the percentage of the contribution of the independent variable leadership style and human resource development to job satisfaction is 0.408 or 40.8 is influenced by variables outside the study while the second equation is 0.720 or 72.0% this shows that the percentage of the contribution of the independent variables of leadership style, human resource development and job satisfaction to the dependent variable of employee performance (Y) is 0.720 or 72, 0%. While the rest is 0.280 or 28.0% influenced by other variables outside of this study.